Rarefied flow regime of an underexpanded supersonic jet - Bykov Nikolay Y.; Gorbachev Yuriy E.; Fyodorov Stanislav A. (E3S Web of Conferences, 2023)
The results of a numerical study of a supersonic underexpanded jet flowing from a conical nozzle into a rarefied environment are presented. The modeling was performed by the direct simulation Monte Carlo method. The range of parameters corresponding to the expansion ratio 40 < n < 240, the hydrodynamic regime of the flow in the nozzle and the rarefied regime of interaction of the jet with the environment, characterized by Knudsen numbers in the range 0.03 < KnL < 0.2, is considered. It is shown that in the specified range of KnL a drastic rearrangement of the flow structure occurs. For the lower limit of the KnL range, a shock-wave structure typical of a highly underexpanded jet is observed. For Kn = 0.2, it completely degrades. Data have been obtained on the process of dimer formation in an expanding jet. An increase in the mole fraction of dimers with increasing distance from the nozzle throat is shown both in the conical nozzle and in the initial section of the jet expansion region.